EPEN-28. NOVEL ONCOGENE AMPLIFICATION IN SPINAL EPENDYMOMA INVOLVING THE MYC LOCUS (8q24). (4th December 2020) - Shatara, Margaret; Boué, Daniel R; Pierson, Christopher R; Thomas, Diana L; Sribnick, Eric A; Jones, Jeremy; Rodriguez, Diana P; Schieffer, Kathleen M; Deeg, Carol; Hamelberg, Elizabeth; LaHaye, Stephanie; Magrini, Vincent; et al.
Abstract: BACKGROUND: We report a unique case of spinal ependymoma with classic histology and aggressive clinical behavior which harbored a focal MYC (8q24) amplification. CASE REPORT: A-12-year old male presented with a three months history of back pain and acute onset weakness with ataxia. A spine MRI revealed an avidly enhancing intradural, extramedullary mass occupying the dorsal spinal canal from C6 through T2. The tumor demonstrated mild diffusion restriction and was associated with severe cord compression and mild edema. He underwent gross total resection. Pathological diagnosis was classic grade II ependymoma. Eleven months later, he re-presented with acute onset lower extremity paresthesia and left-handed weakness. Spine MRI demonstrated tumor recurrence extending from C2 through T1-T2 with resultant severe cord compression, again demonstrating avid enhancement and restricted diffusion. He underwent subtotal resection of the mass and focal proton beam irradiation. MOLECULAR CHARACTERISTICS: The patient was enrolled on an institutional comprehensive genomic profiling protocol. The tumor's copy number profile was complex, including homozygous loss of 17p and notably, amplification of the MYC oncogene. Using fluorescence in situ hybridization, we identified >20 copies of MYC in interphase cells, confirming the gene amplification, while two copies of MYCN (2p24) were seen. DNA methylation further classified this tumor as clustering near posterior fossa group A (score=0.6073) tumors. CONCLUSION: We report a unique case of an adolescent male with aggressive spinal ependymoma harboring focal MYC amplification. Testing for MYC amplification may be reasonable in newly-diagnosed spinal ependymomas to aid in characterization.